Implementasi Project Based Learning pada Pembelajaran IPA di Kelas IV Sekolah Dasar Negeri 42 Pekanbaru - Aisyah, Ridha; Hadiyanti, Putri Octa (Cetta: Jurnal Ilmu Pendidikan, 2025)
Science learning in elementary schools requires strategies that connect the material to students’ real-life experiences to make it more meaningful. Project-Based Learning (PjBL) is one model that encourages active engagement through project completion. This study aims to analyze the implementation of PjBL in science learning on the topic of mung bean growth at SD Negeri 42 Pekanbaru. The research employed a descriptive qualitative method, with the participants consisting of fourth-grade students and the classroom teacher. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings indicate that PjBL can enhance student engagement and foster collaboration, communication, discipline, and responsibility skills. Challenges encountered—such as weak time management, limited information literacy, and lack of presentation experience—can be addressed through teacher mentoring strategies, structured scheduling, provision of additional learning resources, and presentation practice. It can thus be concluded that PjBL is effective in creating meaningful, contextual, and enjoyable science learning while simultaneously fostering independence and 21st-century skills in elementary school students.